PENGARUH KONDISI SOSIAL EKONOMI KELUARGA NELAYAN TERHADAP MINAT ANAK MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI DI DESA TASIKAGUNG KECAMATAN REMBANG (Edu Geography, 2016)
This final project aims to determine the socio-economic conditions and the interest of continuing education to college in fishermen families in the Tasik Agung village, sub-district of Rembang and analyze the influence of socio-economic conditions of fishermen families on the interest of continuing education to college in the village of Tasikagung District of Rembang. The populations of this study are all of children of fishermen families in the Tasik Agung village, sub-districts of Rembang which are on high school, while the sampling is done by double sample with 2 sample respondents as well as the fisherman as parents and his children.. The total samples in this study are 76 include parents and children. Methodology of data collection in this study uses questionnaires/ questionnaire and interview. Methodology of data analysis uses descriptive percentages. Result of this study indicates that socio-economic conditions can affect the interest of the fishermen families to go to college with probability (p) of 0.000 and statistical test (t) 8.853. In conclusion, the educational level of the fishermen in Tasik Agung village is low and will affect the continuation of their children's education into a higher level. Socio-economic condition of the average fisherman is high and will affect the interests of children’s education continuation to college.